Question #57bb0
2 Answers
Explanation:
When Y varies inversely as x, we can express the relationship of such by:
Hence, substituting your values of x and y can give the value of the constant k.
So,
Now that the value of k is known.
Overall, the equation would be:
The question would usually give you a value of
Explanation:
"the initial statement is "yprop1/xthe initial statement is y∝1x
"to convert to an equation multiply by k the constant"to convert to an equation multiply by k the constant
"of variation"of variation
rArry=kxx1/x=k/xlarrcolor(blue)"k is the constant of variation"⇒y=k×1x=kx←k is the constant of variation
"to find k use the given condition"to find k use the given condition
y=45" when "x=7y=45 when x=7
y=k/xrArrk=yx=45xx7=315y=kx⇒k=yx=45×7=315
"equation is " color(red)(bar(ul(|color(white)(2/2)color(black)(y=315/x)color(white)(2/2)|)))